Monitoring plant development after El Niño 1997/98 in northwestern Perú - Richter, Michael; Ise, Michaela (ERDKUNDE, 2005)
This study is based on eight years (1997-2004) of vegetation monitoring of permanent test plots in the arid to semiarid coastal plain of northwestern Perú beginning prior to the last Super-Niño in 1997/98. Sea surface temperature anomalies control regional precipitation patterns, in some cases with surpluses 9000% above normal. In addition to the well-documented El Niño phenomenon, less observed regional anomalies due to Niño-like monsoon effects and La Niña exist. The main focus of the paper is to present climatic impacts on the region´s flora and to document the medium-term impact of El Niño on terrestrial ecosystems. We also focus on regional vegetation dynamics and consequences for the area's food chain. We compare and contrast changes at a coastal desert site and a dry woodland environment 90 km inland. Initially, both sites react similarly to El Niño: short-lived herbs and grasses sprout quickly. But the ongoing succession and retrogression differs in the desert and the woodland due to differences in precipitation at the two sites as well as differences in disturbance regimes (fire and burrowers) and in the intensity of land use. The development of life form spectra as well as spectra of habitat preferences and origin of species also differ between the two sites. Results are discussed in the context of global climate change and are applied to human land use issues where ruderals and non-indigenous species invade and change species composition. We hypothesize that increased ENSO frequency and intensity create greater phytomass that in turn encourages farmers to graze more cattle which leads to degradation with a shift from dry forest to shrub savanna.